Antibodies and Their Receptors: Different Potential Roles in Mucosal Defense - Horton, Rachel; Vidarsson, Gestur (Frontiers in Immunology, 2013)
Over recent years it has become increasingly apparent that mucosal antibodies are not only restricted to the IgM and IgA isotypes, but that also other isotypes and particularly IgG can be found in significant quantities at some mucosal surfaces, such as in the genital tract. Their role is more complex than traditionally believed with, among other things, the discovery of novel function of mucosal immunoglobulin receptors. A thorough knowledge in the source and function and mucosal immunoglobulins is particularly important in development of vaccines providing mucosal immunity, and also in the current climate of microbicide development, to combat major world health issues such as HIV. We present here a comprehensive review of human antibody mediated mucosal immunity.